Iron Diffusion in Electron Beam Melt (EBM) γ-TiAl Based Alloy from the Building Platform: Interface Characterization - Mohammad Saleh Kenevisi; Cristian Ghibaudo; Emilio Bassini; Daniele Ugues; Giulio Marchese; Sara Biamino (Metals, 2023)
Electron beam melting (EBM) is a promising technique for processing γ-TiAl alloys that are susceptible to cracking. TiAl alloys are usually built on stainless steel platforms to reduce overall costs. The interface between the samples and the platform is generally brittle due to the strong diffusion of elements between the two components, making them easily separable just by applying impulsive bending stress. In this work, Ti-48Al-2Cr-2Nb samples were processed via EBM and separated from the platform without altering the interface layer. The interface was studied in four different conditions (as-built, hot isostatic pressed, and solution annealed at 1320 °C and 1360 °C) by using scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and hardness measurement. The results revealed that due to the diffusion of elements such as Fe Cr, and Ni, some hard intermetallics and phases were formed close to the interface of the platform and the first deposited layers, which was confirmed by SEM and XRD. According to the results among all diffusing elements, only Fe could diffuse significantly past the interface. More specifically, the diffusion range in the as-built condition was limited to about 350 μm. However, when the sample was heat treated at 1360 °C, Fe amounts of about 0.7 wt.% was still traced at distances as far as 500 μm. Additionally, annealing at higher temperatures led to more homogeneous and relatively higher hardness values within the matrix. According to the results obtained, removing the samples from the building platform with Electro Discharge Machining (EDM) above the contaminated layer before performing any heat treatment is advised to avoid the removal of thick material layers in order to get back to the nominal alloying composition.